2022
DOI: 10.1097/pgp.0000000000000900
|View full text |Cite
|
Sign up to set email alerts
|

Data Set for the Reporting of Carcinomas of the Vulva: Recommendations From the International Collaboration on Cancer Reporting (ICCR)

Abstract: A cogent and comprehensive pathologic report is essential for optimal patient management, cancer staging, and prognostication. This article details the International Collaboration on Cancer Reporting (ICCR) process and the development of the vulval carcinoma reporting data set. It describes the "core" and "noncore" elements to be included in pathology reports for vulval carcinoma, inclusive of clinical, macroscopic, microscopic, and ancillary testing considerations. It provides definitions and commentary for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…All specimens underwent histopathological review by a surgical pathologist specialized in gynecologic pathology (BD), who confirmed the diagnosis and assessed resection margin status, and the presence of lichen sclerosus (LS) and lymphovascular space invasion (LVSI). In agreement with the recommendations from the International Collaboration on Cancer Reporting (ICCR) [ 4 ], tumors were not graded.…”
Section: Methodsmentioning
confidence: 92%
“…All specimens underwent histopathological review by a surgical pathologist specialized in gynecologic pathology (BD), who confirmed the diagnosis and assessed resection margin status, and the presence of lichen sclerosus (LS) and lymphovascular space invasion (LVSI). In agreement with the recommendations from the International Collaboration on Cancer Reporting (ICCR) [ 4 ], tumors were not graded.…”
Section: Methodsmentioning
confidence: 92%